2018
DOI: 10.1021/acs.iecr.8b05296
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Synthesis Process of an Industrial Ziegler–Natta Catalyst

Abstract: In Ziegler–Natta catalysis, the catalyst particle size has a strong influence not only on catalyst performance but also on the morphology and particle size distribution of the final polymer particles. Fundamental insight into the catalyst particle formation process is therefore of industrial importance when addressing specific requirements in the final products. In the present work, we fully characterize a single-step catalyst preparation process, which comprises a reactive precipitation of a MgCl2-supported Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Titanium is typically included as metal centers of the catalysts and magnesium chloride is widely used for supporting this type of catalysts (Fig. 2) [1,20,21]. Typically, other cocatalysts such as triethyl aluminium are required for activating ZN catalysts so that active sites are created for coordination between metal centers and double bonds of ethylene, after which additions of monomers are repeated for increasing molecular weights of products [22].…”
Section: Ziegler-natta Catalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…Titanium is typically included as metal centers of the catalysts and magnesium chloride is widely used for supporting this type of catalysts (Fig. 2) [1,20,21]. Typically, other cocatalysts such as triethyl aluminium are required for activating ZN catalysts so that active sites are created for coordination between metal centers and double bonds of ethylene, after which additions of monomers are repeated for increasing molecular weights of products [22].…”
Section: Ziegler-natta Catalystsmentioning
confidence: 99%
“…ZN catalysts feature a synthesis of linear UHMWPE due to the low tendency of bimolecular β-hydrogen transfer at low pressure of ethylene, which is one of the advantages over other types of catalysts [22]. While different kinds of ZN catalysts are prepared using distinct methods to optimize catalytic activities, the typical process of preparing this type of catalysts can be mainly generalized into two steps: preparations of supporting complexes and preparations of the catalysts based on the supporting complexes [21]. For example, Antoine et al reported that the addition of ethyl aluminum dichloride (DEAC) could increase particle sizes of catalysts and finally lead to a wider molecular weight distribution [21].…”
Section: Ziegler-natta Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterogeneous conditions for the process use as principal catalytic system the MgCl 2 -supported Ziegler−Natta catalysts, composed of titanium complexes supported onto a MgCl 2 matrix. It is important to stress the use of aluminum alkyls AlR 3 (R = alkyl) as co-catalyst in the polymerization [18].…”
Section: Aluminum: General Properties and Charactermentioning
confidence: 99%